Self-trapping of Fermi and Bose gases under spatially modulated repulsive nonlinearity and transverse confinement - Young-S., Luis E. [UNESP]; Salasnich, L.; Malomed, Boris A. (American Physical Society (APS), 2013)
We show that self-localized ground states can be created in the spin-balanced gas of fermions with repulsion between the spin components, whose strength grows from the center to periphery, in combination with the harmonic-oscillator (HO) trapping potential acting in one or two transverse directions. We also consider the ground state in the noninteracting Fermi gas under the action of the spatially growing tightness of the one- or two-dimensional (1D or 2D) HO confinement. These settings are considered in the framework of the Thomas-Fermi-von Weizsäcker (TF-vW) density functional. It is found that the vW correction to the simple TF approximation (the gradient term) is nearly negligible in all situations. The properties of the ground state under the action of the 2D and 1D HO confinement with the tightness growing in the transverse directions are investigated too for the Bose-Einstein condensate with the self-repulsive nonlinearity. © 2013 American Physical Society.
Keywords: Bose-Einstein condensates; Density functionals; Gradient terms; Spatially modulated; Spin components; Transverse confinement; Transverse directions; Trapping potential; Electron gas; Ground state; Statistical mechanics; Fermions